PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN CEPAT SAJI KENTUCKY FRIED CHICKEN JAKARTA UTARA - Yati Kusmawati; Bonifasius MH Nainggolan; Verry Cyasmoro (LPPM and Travel Operation Department Universitas Asa Indonesia, 2019)
This study analyzes the effect of Brand Equity on purchasing decisions at fast food restaurants Kentucky Fried Chicken North Jakarta. The basic concepts of Brand Equity which are variables in this study are Brand Awareness (X1) Quality Perception (X2), Brand Association (X3) and Brand Loyalty (X4). Whereas the Purchase Decision is denoted as Y variable. The data used in this study are primary data and secondary data. Primary data was collected using a study questionnaire and five measurements of variables examined on five levels of Likert scale. Respondents were taken from 120 consumers of the KFC restaurant in North Jakarta with the requirement to have made purchases at the restaurant more than twice. The method used in this study is quantitative statistics, using multiple linear regression analysis. The results showed that there were significant influences between Brand Awareness, Quality Perception, Brand Association, Brand Loyalty on Purchase Decisions partially and simultaneous